What's pushing international tourism expenditures? - Christoph Vietze (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
In this paper we discuss the determinants which contribute to outbound tourism expenditures. The aim is to show whether and how different socio-economic factors in countries of origin are responsible for the demand, to spent money for tourist activities in foreign countries. While we are able to find a strict robust positive impact of all economic factors like the per capita income and the openness to trade on the tourism expenditures per capita as well as on the tourism expenditure per GDP, most of the sociological factors show rather a weak significance. However, there seems to be somewhat like a corporate openness to tourism as countries which are able to attract high inbound tourism receipts per capita also having high outbound tourism expenditures per capita as well. A further important finding is that people in democratic countries with a high level of civil rights spend a higher share of income for traveling abroad. Our results give us an indirect and encouraging hint that it makes sense for developing countries to sustainable invest in the tourism sector as an increasing willingness to pay for outbound tourism goes hand in hand with an increasing per capita income in the world.
Keywords: F14; F18; 330; Tourism; tourism expenditures; economic growth; Tourismus; Verbraucherausgaben; Wirtschaftswachstum; Lebensstandard; Demokratie; Welt